Increasing Financial Management Awareness of Indonesian Immigrant Workers in Taiwan Through Training Activities - Ignatius Oki Dewa Brata; Bunga Indah Bayunitri; H. R. Roosaleh Laksono T. Y.; Eriana Kartadjumena (IJECS: Indonesian Journal of Empowerment and Community Services, 2025)
ABSTRACT Limited understanding of financial management among Indonesian migrant workers (IMWs) in Taiwan often leads to financial instability, both during their employment and after returning home. One of the main contributing factors is the lack of access to financial education. This community service program aims to enhance the financial awareness and management skills of IMWs through a series of structured training activities. The method involved five key stages: needs assessment, material preparation, training implementation, mentoring, and outcome evaluation. The training included interactive lectures, financial simulations, and group discussions. The results showed a significant improvement in participants' understanding of basic financial management, debt control, and long-term financial planning, supporting their path toward financial independence. Kata kunci: Indonesian migrant workers, financial training, community service, financial awareness, Taiwan.